2004
DOI: 10.1016/j.micpath.2003.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow colony-formation in vitro after infection of genetically defined inbred mice with Candida albicans

Abstract: The effect of C. albicans infection on the production of haematopoietic precursor cells in the bone marrow of CBA/CaH and BALB/c mice was evaluated by assay of colony formation in vitro. In immunocompetent mice, neither systemic nor oral infection induced significant alterations in colony formation by bone marrow from the two mouse strains, and Candida infection did not alter the proportion of morphological cell types in the colonies. However, the number of neutrophil-like was relatively greater in colonies de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…In addition, in the functional tests, we found that dectin-1 activation inhibited bone resorption of RANKL-induced osteoclasts. These results are consistent with previous observations that intravenous injection with Candida albicans enhanced new bone formation in mice [ 24 ], and dectin-1 activation in osteoclast precursors inhibited RANKL-induced osteoclast differentiation in vitro [ 18 ]. Furthermore, curdlan treatment failed to suppress dectin-1 −/− osteoclast differentiation.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, in the functional tests, we found that dectin-1 activation inhibited bone resorption of RANKL-induced osteoclasts. These results are consistent with previous observations that intravenous injection with Candida albicans enhanced new bone formation in mice [ 24 ], and dectin-1 activation in osteoclast precursors inhibited RANKL-induced osteoclast differentiation in vitro [ 18 ]. Furthermore, curdlan treatment failed to suppress dectin-1 −/− osteoclast differentiation.…”
Section: Discussionsupporting
confidence: 93%
“…Neutrophils are known to be an important effector cell in Candida infection and CBA/CaH nude mice with chronic oral infections have a depleted colony‐forming response in vitro when compared with BALB/c 17 . As this suggested that neutrophil precursors might be a limiting factor in the susceptibility of this strain, the quantitative production of neutrophils in vitro by bone marrow derived from the two mouse strains was compared in a double‐cross‐over experiment.…”
Section: Resultsmentioning
confidence: 99%
“…Neutrophils are known to be an important effector cell in Candida infection and CBA/CaH nude mice with chronic oral infections have a depleted colony-forming response in vitro when compared with BALB/c. 17 As this suggested that neutrophil precursors might be a limiting factor in the susceptibility of this strain, the quantitative production of neutrophils in vitro by bone marrow derived from the two mouse strains was compared in a double-cross-over experiment. Generation of neutrophils by differentiation of BALB/c bone marrow cells on a BALB/c stromal cell layer produced the greatest yield (mean ± SD: 97.0 ± 7.6´10 5 cells/culture), whereas neutrophil production by BALB/c bone marrow cells on a CBA/CaH stromal cell layer was significantly less (44.6 ± 5.5, P < 0.001).…”
Section: Neutrophil Production From Bone Marrow Culturementioning
confidence: 99%
“…A possibility for which there is some evidence is that T cells act to enhance production of phagocytic cells by the bone marrow. Studies in chronically orally-infected nude mice have demonstrated that bone marrow colony formation in vitro is significantly depressed in the CBA/CaH mice compared to BALB/c (26). Reconstitution with T cells significantly increased the colony-forming response in BALB/c, but not in CBA/CaH mice.…”
Section: Oral Candidiasismentioning
confidence: 99%